Interfaith Marriage in North Lombok: Sociological Perspective of Islamic Law - Khairul Hamim; Muhammad Iskandar; Muhammad Azizurrohman (Khazanah Hukum, 2022)
Interfaith marriage has no legal foundation. However, this marriage practice is still carried out among the people of North Lombok. Using a purposeful sampling methodology, the authors used a descriptive qualitative method to collect data from several interviewees, including village heads, religious leaders, and interfaith marriage players. According to this study, interfaith marriage requires the bride to follow the religion of her prospective spouse. Environmental factors, kinfolk or kindred, married by accident, sociocultural factors, a lack of religious knowledge, and transmigration all contribute to this marriage. At the very least, this marriage psychologically affects spouses and families. It also has an impact on the religious peace of the surrounding communities. In the meantime, interfaith leaders advise against interfaith weddings.